2008
DOI: 10.2214/ajr.07.2784
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Whole-Breast Vascularity with Ipsilateral Breast Cancers Using Contrast-Enhanced MDCT

Abstract: ing tumor. However, vascularity can increase not only within a breast cancer lesion but also in the ipsilateral breast as a whole. Recently, some studies have estimated whole-breast vascularity by laser Doppler perfusion imaging [15], PET [16], and MRI [17][18][19] and found an association between breast cancer and an ipsilateral increase of blood flow.Although contrast-enhanced CT of the breast has been used for assessment of axillary lymph node metastasis [20,21], diagnosis of local recurrence after breast-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…We also evaluated the usefulness of IIWBV for an early prediction of the response, because our previous study identified IIWBV as predicting poor prognostic indicators (tumor size, lymph node status, and nuclear and histological grade). 26,38 In this study, however, there was no significant difference (P = 0.068) in the degree of IIWBV on baseline or follow-up MRI between responders and nonresponders. Furthermore, the change in IIWBV after NAC was not correlated with the response (P = 0.081).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…We also evaluated the usefulness of IIWBV for an early prediction of the response, because our previous study identified IIWBV as predicting poor prognostic indicators (tumor size, lymph node status, and nuclear and histological grade). 26,38 In this study, however, there was no significant difference (P = 0.068) in the degree of IIWBV on baseline or follow-up MRI between responders and nonresponders. Furthermore, the change in IIWBV after NAC was not correlated with the response (P = 0.081).…”
Section: Discussioncontrasting
confidence: 69%
“…The degree of vascularity differences was classified as ''prominent'' if the number of vessels in the cancer-bearing breast was higher by 3 or more than those in contralateral breast, ''moderate'' if higher by 2, ''mild'' if higher by 1, and ''not increased'' if the number of vessels in ipsilateral breast was same as or lower than that of contralateral breast. 26 …”
Section: Breast Mri Analysismentioning
confidence: 99%
“…Different imaging modalities were used for imaging increased vascularity, for example, laser Doppler perfusion imaging [18], positron emission tomography [19], computed tomography (CT) [20] and MRI [46, 8, 10, 2123]. With respect to MRI, most researchers use one of two methods to assess changes in vascularity in the presence of malignancy.…”
Section: Discussion and Further Perspectivesmentioning
confidence: 99%
“…Previous studies have been carried out on this subject. Studies comparing whether vascularization in the breast with lesion is increased in comparison with the contralateral breast through subjective methods without measuring vessel diameters are in the majority (10)(11)(12). In a study by Kang et al (11) it has been observed that vascularization has increased globally in the breast with lesion; however, vascular diameter has not been addressed, and only malignant cases were included in the study.…”
Section: Discussionmentioning
confidence: 99%